Elite Victimization: A Positivist Victimology Analysis of the August 2025 Looting of Official Homes in the Frame of Social Media Framing - Mohamad Aflah Muna Ananda; Faizul Kamali Al Asyih (Faculty of Law, Universitas Lampung, 2025)
The looting of state officials’ residences represents a distinct form of social conflict in which political elites become victims of collective violence. This study analyzes how officials’ actions and policies contributed to victim precipitation during the August 2025 looting and how social media framing transformed this process into perceived moral legitimacy. Using a juridical–normative method with qualitative analysis of victimology theory, legal norms, and academic literature, the study finds that officials retain legal victim status but are socially perceived as contributing to their victimization through unpopular policies and controversial public conduct. This contribution is mediated and amplified by social media framing, which shapes public opinion and reframes looting as a form of “social correction.” The findings confirm the relevance of positivist victimology in the digital era while highlighting the role of digital platforms in constructing victimization. The study recommends integrating victimological perspectives into victim protection policies and strengthening ethical public communication by state officials.